2012
DOI: 10.1111/ijcs.12003
|View full text |Cite
|
Sign up to set email alerts
|

Financial socialization's impact on investment orientation and household net worth

Abstract: This study investigates the role of financial socialization for investment orientation and household net worth. Combining consumer socialization literature with findings in the behavioural finance literature, survey data were analysed to (1) investigate the relationship among household net worth, financial socialization, indicators of investment orientation and socio-demographic investor characteristics; (2) examine the influence of sociodemographic investor characteristics and financial socialization on indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 26 publications
3
65
0
6
Order By: Relevance
“…They conclude that when it comes to different parental teaching strategies: "the more the better". Further, Hira et al (2013) establish that financial socialization by the parents is positively associated with household net wealth and the tendency to invest regularly.…”
Section: Financial Socialization By Parentsmentioning
confidence: 90%
“…They conclude that when it comes to different parental teaching strategies: "the more the better". Further, Hira et al (2013) establish that financial socialization by the parents is positively associated with household net wealth and the tendency to invest regularly.…”
Section: Financial Socialization By Parentsmentioning
confidence: 90%
“…Explicit financial teaching via discussion has also been found to be associated with children's financial learning and future behaviors . For example, compared with their counterparts, adults whose parents engaged in financial discussion when they were children tend to have less credit card debt (Grinstein-Weiss et al, 2011;Norvilitis & MacLean, 2010), less loan delinquency and a lower rate of home foreclosure (Grinstein-Weiss et al, 2012), higher credit scores (Grinstein-Weiss et al, 2011), and higher household net worth and rate of investing (Hira et al, 2013). Similarly, Bucciol and Veronesi (2014) found that adults whose parents taught them to save during childhood were 16% more likely to save, and their savings were 30% more than their counterparts who were not taught.…”
Section: Howsmentioning
confidence: 99%
“…Parents have the greatest impact on children's financial learning (Clarke et al, 2005;Grinstein-Weiss et al, 2012;Jorgensen & Savla, 2010;Serido, Shim, Mishra, & Tang, 2010) and therefore on future financial capability and independence (Grinstein-Weiss, Spader, Yeo, Key, & Freeze, 2011;Hira, Sabri, & Loibl, 2013). In recent years, emerging and young adults have been struggling to achieve financial capability and independence (Clarke et al, 2005;Lusardi, Mitchell, & Curto, 2010).…”
mentioning
confidence: 99%
“… 28 Other studies discussing financial socialization of the young include Hira, Sabri, and Loibl (2013) and the references cited therein. …”
mentioning
confidence: 99%